Pandangan Mahasiswa Fusi Tentang Peran Tauhid Dan Filsafat Islam (Tuhan Dan Alam Semesta) - Muhammada Fathi Aswan; Adenan Adenan; Nabilah Batubara; Khoirotunnisa Aulia; Siti Lailatul Jannah; Mhd Akhir Harahap; Annisa Suhiya Putri; Salman Faris Dalimunthe; Brylian Velis Efendi Ritonga; Anggi Syahputra; Ilham Hasan; Muhammad Rizky Harahap; Suci Fatmala (Journal of Innovative and Creativity, 2026)
This study aims to examine the perspectives of students from the Faculty of Ushuluddin and Islamic Studies (FUSI) regarding the role of tawhid and Islamic philosophy in understanding the concept of God and the universe. Tawhid, as the core foundation of Islamic teachings, is closely connected to Islamic philosophy in constructing a rational and theological framework for comprehending divine reality and the relationship between God and creation. This research employs a qualitative approach with a descriptive-analytical method. Data were collected through open-ended questionnaires and brief interviews with purposively selected FUSI students. The collected data were analyzed using thematic analysis to identify recurring ideas and patterns in students’ responses. The findings indicate that FUSI students perceive tawhid not merely as a normative doctrine, but also as a philosophical principle that explains the order of the universe and the relationship between God and His creation. Islamic philosophy is understood as a reflective tool that strengthens the rational and contextual understanding of tawhid. This study is expected to contribute academically to the development of tawhid and Islamic philosophy studies among university students.